2015
DOI: 10.1124/jpet.115.226639
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Epithelial-Mesenchymal Transition via Activation of Epidermal Growth Factor Receptor Contributes to Sunitinib Resistance in Human Renal Cell Carcinoma Cell Lines

Abstract: Sunitinib is widely used for treating renal cell carcinoma (RCC). However, some patients do not respond to treatment with this drug. We aimed to study the association between sunitinib sensitivity and epithelial-mesenchymal transition (EMT) regulation via epidermal growth factor receptor (EGFR) signaling, which is a mechanism of resistance to anticancer drugs. Three RCC cell lines (786-O, ACHN, and Caki-1) were used, and then we evaluated cell viability, EMT regulatory proteins, and signal transduction with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…Hypoxia has traditionally been viewed as a consequence of malignant tumor growth, and it is now widely appreciated to play a critical role in the development and progression of tumors . It has been reported that long‐term treatment with VEGFR2 kinase inhibitors may cause tumor progression, partially because of hypoxia‐induced epithelial to mesenchymal transition (EMT) . However, some reports have shown that VEGFR inhibitors significantly inhibit hypoxia‐induced EMT and tumor progression .…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia has traditionally been viewed as a consequence of malignant tumor growth, and it is now widely appreciated to play a critical role in the development and progression of tumors . It has been reported that long‐term treatment with VEGFR2 kinase inhibitors may cause tumor progression, partially because of hypoxia‐induced epithelial to mesenchymal transition (EMT) . However, some reports have shown that VEGFR inhibitors significantly inhibit hypoxia‐induced EMT and tumor progression .…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, many basic pre-clinical RCC studies employing functional research on “renal cancer/renal carcinoma/renal adenocarcinoma/renal cell cancer” cell lines do not analyze the background of the investigated model and analyze different subtypes of RCC together, including wild-type cell lines and those harboring mutations (i.e. VHL) and cell lines of different histotypes [2123]. The conclusions of such projects may be difficult to interpret, and the value of potential therapeutic targets is rather questionable, as is the true relevance to a particular RCC.…”
Section: Introductionmentioning
confidence: 99%
“…3A and 3B). Mizumoto et al [27] suggested that acquired resistance to sunitinib in RCC cells may be related to the activation of EGFR, and thus, increased EGFR in the SNU-333 cells might have a role in resistance, as well as sphere formation.…”
Section: Discussionmentioning
confidence: 99%